The Prospects of Ecologically Clean Farming Production in the Cross-Border Areas of the Great Altai - Kundius, Valentina Aleksandrovna; Glotko, Andrey Vladimirovich; Galkin, Denis Gennadyevich (International Journal of Economics and Financial Issues, 2015)
The scientific foundations of farming focused on ecologically clean production have been developed. The concept and management mechanism of the development of farming focused on ecologically clean production have been formed. The institutional mechanism of the strategic development of the velvet antler deer breeding industry in the Altai Region and the Republic of Altai has been improved and tested; as opposed to the existing ones, it has been supplemented by a scenario approach to planning and forecasting. The proposals for strategic development of regional velvet antler deer breeding of the Altai Region and the Republic of Altai have been made forward. Based on stage-by-stage method, the most probable scenario of velvet antler deer breeding development has been proposed and a normative model of the velvet antler deer breeding industry status has been developed. Keywords: ecologically clean farming production, organic product market model, efficiency of regional velvet antler deer breeding industry, strategic development of velvet antler deer breeding industry, development indices JEL Classifications: Q12, Q57, R11